Perceived threat and coping responses during the COVID-19 pandemic: Prospective associations with vaccine hesitancy. Issue 52 (12th December 2022) - Morstead, Talia; Zheng, Jason; Sin, Nancy L.; DeLongis, Anita
Highlights: Ways of coping with the threat of COVID-19 predicted subsequent vaccine hesitancy. Avoidance coping was associated with subsequent vaccine hesitancy. Low perception of COVID-19 threat was associated with subsequent vaccine hesitancy. Approach coping reduced vaccine hesitancy among those perceiving low COVID-19 threat. Coping responses may serve as targets for intervention to reduce vaccine hesitancy. Abstract: Background: The COVID-19 pandemic has brought to light the importance of identifying factors associated with vaccine hesitancy. Disease threat and coping responses are central to health behavior engagement and present potential alterable targets for intervention. Purpose: To examine the roles of perceived threat of COVID-19 and coping in vaccine hesitancy, we examined how coping strategies involving approach and avoidance interact with perceived threat of COVID-19 to predict vaccine hesitancy. Methods: We used data from 1570 North American participants who reported their vaccine hesitancy as part of a longitudinal study assessing psychosocial responses to the pandemic. We used logistic regression models and mean scores of perceived threat of COVID-19, approach coping, and avoidance coping from prior timepoints to predict vaccine hesitancy in December 2020, when COVID-19 vaccines were first being approved for use in North America. Results: Low perceived threat of COVID-19 was associated with greater likelihood of being vaccine hesitant. However, approach coping moderated this association, such that people who engaged in more approach coping were less likely to be vaccine hesitant even when they did not feel personally threatened by COVID-19. In contrast, avoidance coping was associated with greater likelihood of vaccine hesitancy regardless of perceived threat of COVID-19. Conclusions: Our results illustrate the contributions of approach and avoidance coping to vaccine hesitancy and in doing so, provide preliminary evidence for coping behavior to serve as a target for intervention to reduce vaccine hesitancy.